Pulmonary embolism and in situ pulmonary artery thrombosis in paediatrics - Rajpurkar, Madhvi; Biss, Tina T.; Amankwah, Ernest K.; Martinez, Denise; Williams, Suzan; van Ommen, C. Heleen; Goldenberg, Neil A. (Thrombosis and Haemostasis, 2017)
Data on paediatric pulmonary embolism (PE) are scarce. We sought to systematically review the current literature on childhood PE and conducted a search on paediatric PE via PubMed (1946–2013) and Embase (1980–2013). There was significant heterogeneity in reported data. Two patterns were noted: classic thromboembolic PE (TE-PE) and in situ pulmonary artery thrombosis (ISPAT). Mean age of presentation for TE-PE was 14.86 years, and 51% of cases were males. The commonest method for diagnosis of TE-PE was contrast CT with angiography (74% of patients). The diagnosis of TE-PE was often delayed. Although 85% of children with TE-PE had an elevated D-dimer at presentation, it was non-discriminatory for the diagnosis. In paediatric TE-PE, the prevalence of central venous catheters was 23%, immobilisation 38%, systemic infection 31% and obesity 13%, elevated Factor VIII or von Willebrand factor levels 27%, Protein C deficiency 17%, Factor V Leiden 14% and Protein S deficiency 7%. In patients with TE-PE, pharmacologic thrombolysis was used in 29%; unfractionated heparin was the most common initial anticoagulant treatment in 64% and low-molecular-weight heparins the most common follow-up treatment in 83%. Duration of anticoagulant therapy was variable and death was reported in 26% of TE-PE patients. In contrast to TE-PE, patients with ISPAT were not investigated systematically for presence of thrombophilia, had more surgical interventions as the initial management and were often treated with anti-platelet medications. This review summarises important data and identifies gaps in the knowledge of paediatric PE, which may help to design future studies.
Keywords: Pulmonary embolism; pulmonary artery thrombosis; paediatrics; children